A protocol for an experimental investigation of the effects of pain-related interpretation bias modification on interpretation of ambiguous somatosensory and linguistic stimuli in healthy individuals - Philippa Broadbent; Christina Liossi; Daniel Eric Schoth (PLoS ONE, 2025)
Researchers are increasingly exploring the existence and potential implications of pain-related cognitive biases in clinical and non-clinical populations, using a range of paradigms and stimuli to test theoretical predictions and refine models. One avenue of investigation explores the implications of biased pain-related interpretations in pain-free individuals, which may shed light on processes of transition from a pain-free state to acute pain, and acute pain to chronic pain. The primary aim of the main study detailed in this protocol is to investigate the effects of pain-related cognitive bias modification for interpretation (CBM-I) on the interpretation of ambiguous somatosensory stimuli. When deciding the point at which to report their level of pain threshold and tolerance, participants must by necessity interpret somatosensory sensations. Sensations around the pain threshold are likely to be ambiguously painful, sometimes interpreted as painful and sometimes not, which has been proposed as a zone of uncertainty. A pilot study was first conducted to test whether the proposed experimental design is feasible and appropriate, and to ascertain study effect sizes. Eighteen healthy participants were randomised to complete either benign CBM-I (trained towards neutral interpretations of ambiguous scenarios; n =  9) or pain CBM-I (trained towards pain-related interpretations of ambiguous scenarios; n =  9). The Ambiguous Scenarios Task was used to train interpretation biases, and a novel Interpretation of Somatosensory Sensations Assessment was used to explore interpretation of ambiguous somatosensory sensations around the individual’s pain threshold. Participants receiving pain CBM-I, compared to those receiving benign CBM-I, had higher pain-related interpretation bias scores on the test phase of the Ambiguous Scenarios Task with a large effect size, and showed higher intensity and unpleasantness ratings on the Interpretation of Somatosensory Sensations Assessment typically with medium to large effect sizes. These paradigms are suitable for a full-scale investigation. Modifications made to the experimental design based on insights from the pilot study are discussed. This research extends beyond pain patient populations to researchers and clinicians working with other conditions, especially anxiety and mood disorders where patients may misinterpret or catastrophize ambiguous bodily sensations.